Molecular epidemiological studies on avian pathogenic Escherichia coli associated with septicemia in chickens in India. (January 2022) - Narasinakuppe Krishnegowda, Dharanesha; Singh, Bhoj Raj; Mariappan, Asok Kumar; Munuswamy, Palanivelu; Singh, Karam Pal; Monalisa sahoo; Saminathan, Mani; Ramalingam, Rajasekar; Chellappa, Madhan Mohan; Singh, Vidya; Dhama, Kuldeep; Reddy, Maddula Ramakoti
Abstract: Bacterial septicemia causes huge economic losses in the poultry industry and there is no systematic research available in India on the connection of various pathogens associated with septicemia. The present molecular epidemiological study was conducted to investigate the association of different bacterial and immunosuppressive viral pathogens in septicemia suspected chickens. A total of 443 chicken carcasses with septicemic conditions from 71 different flocks were included in this study. Heart blood swabs were subjected to bacterial culture for Salmonella spp., Pasteurella multocida, Escherichia coli, and Gallibacterium anatis . Of these 51 flocks tested for E. coli, 49 (96.1%) flocks were found positive. Among flocks tested for Salmonella spp., 2 flocks were found positive. All tested flocks were found negative for G. anatis and P. multocida as well as air sac swabs tested negative for Mycoplasma spp. Bacterial cultural examination revealed that majority of septicemic chickens were found to be infected with E. coli and these E. coli isolates showed the highest resistance to vancomycin (60%), followed by erythromycin (50%) and cefotaxime (38%) and maximum sensitivity to cefotaxime and clavulanic acid combinations (81.5%), followed by chloramphenicol (69.6%) and ertapenem (67.2%). Among the 5 avian pathogenic E. coli (APEC) virulence genes were detected in 36 flocks and highest frequency of iss (100%), followed by ompT or iutA (97.2%), hly (61.1%) and iroN (47.2%) genes. On polymerase chain reaction (PCR) screening, 10.5, 4.5, 52.2, 19.4, 9.0, 4.5, 20.1 and 19.4% of the flocks were positive for G. anatis, Ornithobacterium rhinotracheale, APEC, Salmonella spp., Mycoplasma gallisepticum, Mycoplasma synoviae, chicken infectious anemia virus and Marek's disease virus, respectively. To our knowledge, the present study is first on the etiology of septicemia in chicken flocks in India. The present study infers that the majority of septicemic deaths in broiler chickens less than 8 weeks have been connected with APEC and majority of E. coli isolates are multidrug resistance, suggesting the need for surveillance and intervention to curb the inadvertent use of antibiotics. Although, incidence of G. anatis association with septicemia was reported, still requires a rigorous epidemiological study to determine the actual prevalence. However, more detailed studies encompassing vast geographical area with large sample size and long duration of the studies are necessary to provide a clear picture of the interaction of different pathogens causing septicemia in chicken. Highlights: APEC is most commonly associated with septicemia in chickens. The frequencies of occurrence of different VAGs such as iroN, ompT, hly, iss and iutA genes in the APEC was 47.2, 97.2, 61.1, 100, and 97.2%, respectively. The E. coli isolates showed the highest resistance to vancomycin (61%) and high sensitive to cefotaxime/clavulanic acid combination. Gallibacterium anatis detected in septicemic chickens by PCR.